The Associated worker cooperatives in Valle del Cauca and their contribution to the region’s economy: A critical judgment based on empirical evidence - De Llano Feliú, Josefina Mayra; Galindez Reyes , Angela María; Grajales Gomez , Juliana (Cooperativismo & Desarrollo, 2022)
The article pretends to make a characterization of the cooperative sector in the Valle del Cauca, focusing on worker cooperatives (CTA), considering that this type of association generates an important contribution to the economic and social development of the region, creating opportunities with positive results as a response to the social and economic crises of the country. With a mixed approach and descriptive character, both quantitative and qualitative elements are considered, which are susceptible to be measured through instruments designed for this purpose. Based on the results obtained, it is concluded that, in order to promote the creation of CTA in the region, it is necessary for government entities to create strategies that make this type of associativity visible by approaching cooperativism as an opportunity for economic, social and cultural development. On the other hand, empirical evidence shows that even though there is social recognition of the cooperative sector, particularly worker cooperatives, are not sufficiently widespread in the region and progress in their promotion is insufficient despite the efforts of the governing bodies of the solidarity sector.
Keywords: solidarity economy; associated work cooperatives; cooperativism; associativity